Maternal transmission of a rare GABRB3 signal peptide variant is associated with autism - Delahanty, Ryan J. (2009)
Maternal 15q11-q13 duplication is the most common copy number variant in autism, accounting for ∼1-3% of cases. The 15q11-q13 region is subject to epigenetic regulation and genomic copy number losses and gains cause genomic disorders in a parent-of-origin-specific manner. One 15q11-q13 locus encodes the GABA(A) receptor β3 subunit gene (GABRB3), which has been implicated by several studies in both autism and absence epilepsy, and the co-morbidity of epilepsy in autism is well established. We report that maternal transmission of a GABRB3 signal peptide variant (P11S), previously implicated in childhood absence epilepsy, is associated with autism. Analysis of wild-type and mutant β3 subunit-containing α1β3γ2 GABA(A) receptors demonstrates reduced whole cell current and decreased β3 subunit protein on the cell surface due to impaired intracellular β3 subunit processing. We thus provide the first evidence for association between a specific GABA(A) receptor defect and autism, direct evidence that this defect causes synaptic dysfunction that is autism-relevant, and the first maternal risk effect in the 15q11-q13 autism duplication region linked to a coding variant.